Morphological Component of Uterine Leiomyoma Pathogenesis - Andrey Gayday (Journal of Global Pharma Technology, 2018)
It was shown that the pleonasm of myoma myocytes is one of the main processes that cause an increase in the mass of the tumor. In spite of the fact that momentous cells show similarity with cells of the myometrium, differences in the structure and metabolism of these tissues were unearthed. The paper presents an analysis of the morphological structure of uterine leiomyoma with a view to establishing its pathogenesis. 93 in-treatment patients diagnosed with uterine myoma took part in the research. 60 extirpated uteruses were morphologically investigated. The statistical processing of data included estimation of the arithmetic mean (M), the average error of mean (m) as well as the frequency of the occurrence of features with discrete values. Student’s t-test was used as well as Pearson’s chi-squared test and Fisher’s exact test, the method of multiple intergroup differences, multiple regression analysis and linear discriminant analysis. The modern studies substantially expand our idea of the risk factors and the mechanisms of development of uterine leiomyoma. A comprehensive approach to the study of the myoma provides new data on the prevalence and causes of this disease. One of the main outcomes of the analysis of contemporary data on uterine leiomyoma is the fairly clear interdependence between the character of the growth and the enlargement the tumor as well as the development of multifaceted changes on the systemic and local levels.Keywords: Myoma, Uterus, Reproduction, Histology, Histochemistry, Etiology, Degeneration, Cell Necrobiosis, Denervation.